Efektivitas Program Sijariemas Terhadap Penanganan Kasus Kegawatdaruratan Maternal: The Effectiveness of the Sijariemas Program in Handling Maternal Emergency Cases - Muayanah (Dohara POAJ, 2023)
Introduction: The maternal mortality rate (MMR) in Indonesia or in Tangerang Regency remains high and does not reach the MDGs targets. There are many programs to reduce MMR including the gold program. One of the components of the gold program is Sijareiams (Maternal and Neonatal Referral Network Information System). It is hoped that Sijariemas can reduce MMR by preventing '3 Delays' especially being late to refer and receive treatment. The Kresek Health Center in Tangerang Regency is one of the Community Health Centers that uses the program but the effectiveness of the program is unknown. The purpose of writing is to determine the effectiveness of the Sijariemas program for handling maternal emergency cases at the Kresek Health Center in Tangerang Regency in 2022. Methods: Qualitative descriptive with a case study approach. Collecting data using in-depth interviews and observation. Results: The results of the Sijariemas program analysis based on input and output found no problems while the implementation process found network problems. Discussion: The Sijariemas program in handling maternal emergency cases has been running smoothly and well it's just that Sijariemas users still don't fully carry out the procedure correctly. It is hoped that there will be a thorough outreach starting from the village, health center, and hospital to the health office so that the program can be implemented smoothly without any problems.